UNDERSTANDING THE UNIQUE OF THE HARVEST PARTY TRADITION MAJJENE-JENNE IN BARRU DISTRICT - M, A. Pananrangi; Ariyadi, A.; Ismail, Andi Muhammad Ishak (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 The Visual journal